Bipolar Cauterization of Significant Access Tract Bleeding during Percutaneous Nephrolithotomy and Its Outcomes (Bangladesh Journal of Urology, 2026)
Introduction & Objectives: Percutaneous nephrolithotomy (PCNL) is a minimally invasive procedure and the gold standard for kidney stone larger than 2cm, complex renal stone and upper ureteric stone. Most of the urologist use nephrostomy tube after standard percutaneous nephrolithotomy for drainage, hemostasis and tract healing purpose. Recently some urologist avoiding this tube placement. Placement of nephrostomy tube may lead to urinary leakage. In Nephrostomy free PCNL, bleeding is one the most serious complication in early post operative period. We perform the bipolar cauterization of significant bleeding point to keep the PCNL tract bloodless. We aimed to evalute the efficacy and safety of bipolar cauterization of tract bleeding during percutaneous nephrolithotomy.Materials and Methods: This study is a prospective study conducted in Metropolitan speciality centre for kidney diseases & urology, Chattagram from March 2023 to March 2025. Total 314 patients underwent supine tubeless PCNL in the form of standard and miniperc.  Out of which, in (group-1) 82 cases following standard tubeless PCNL with significant tract bleeding, bipolar cauterization performed following screening of tract. Rest 232 cases (group 2) following tubeless PCNL tract closure done without cauterization due to insignificant bleeding. Two groups were divided on the basis of severity of tract bleeding. We used 24 fr amplatz sheath during standard PCNL. We defined tract site bleeding as, When bleeding starts across the tract and obscure the vision while withdrawing the amplatz sheath after completion of procedure. Bleeding point was checked and cauterized. We used bipolar resectoscope inner sheath assembled with irrigation port and working element with cutting loop/ roller ball for specific cauterization of bleeding point. Bleeding point was checked and cauterized after placement of D-J stent. No use of Nephrostomy tube.  All data were collected and statistically analyzed.Result: In demographic characteristics, male was predominate in both group 64.63% vs 65.52% and mean age was 39.82 ± 12.6 vs 42.3±12.81 years. In terms of stone clearance in both group, there is no significant difference. Mean stone size 3.14±1.8 cm vs 3.98±1.5cm. Mean operative time 68.57±15.8 min vs 60.12±13.3 min, Postoperatively 1.21% ( 1 case) in group 1 where 5.17% ( 12 cases) in group-2 required blood transfusion. Hospital stay was less in group-1 but statistically not significant. Transient hematuria (within 1st 24 hours) was numerically higher in group-2 but statistically not significant. Minor complications like fever (8.53% vs 12.5%) and urinary tract infection (9.75% vs 9.05%) developed in both both group.Conclusion: Bipolar cauterization of bleeding point in PCNL access tract at the end of the procedure make the tract bleeding less and reduce the hospital stay, analgesic requirement, need of blood transfusion. This modification of bleeding control is safe and effective and provide a more secure procedure.Bangladesh J. Urol. 2025; 28(2): 79-84